Objective CT-Based Quantification of Lung Sequelae in Treated Patients With Paracoccidioidomycosis - Alvarez, Matheus [UNESP]; Miranda, Diana Rodrigues de Pina [UNESP]; Oliveira, Marcela de [UNESP]; Ribeiro, Sergio Marrone [UNESP]; Mendes, Rinaldo Poncio [UNESP]; Duarte, Sergio B.; Miranda, Jose R. A. [UNESP] (Lippincott Williams & Wilkins, 2014)
This study presents methodology for objectively quantifying the pulmonary region affected by emphysemic and fibrotic sequelae in treated patients with paracoccidioidomycosis. This methodology may also be applied to any other disease that results in these sequelae in the lungs.Pulmonary high-resolution computed tomography examinations of 30 treated paracoccidioidomycosis patients were used in the study. The distribution of voxel attenuation coefficients was analyzed to determine the percentage of lung volume that consisted of emphysemic, fibrotic, and normal tissue. Algorithm outputs were compared with subjective evaluations by radiologists using a scale that is currently used for clinical diagnosis.Affected regions in the patient images were determined by computational analysis and compared with estimates by radiologists, revealing mean (+/- standard deviation) differences in the scores for fibrotic and emphysemic regions of 0.1% +/- 1.2% and +/- 0.2% +/- 1.0%, respectively.The computational results showed a strong correlation with the radiologist estimates, but the computation results were more reproducible, objective, and reliable.